(x+1)(2x+1)+2(x-1)(x+3) = -5
Răspunsuri la întrebare
Răspuns de
1
2x²+x+2x+1+2(x²+3x-x-3)=-5
2x²+x+2x+1+2x²+6x-2x-6=-5
4x²+7x-5=-5
4x²+7x=-5+5
4x²+7x=o
S=Ф
2x²+x+2x+1+2x²+6x-2x-6=-5
4x²+7x-5=-5
4x²+7x=-5+5
4x²+7x=o
S=Ф
Răspuns de
1
2x la a doua + 2x+x+1+2(x la a doua -x +3x -3=-5
2x la a doua + 2x+x+1+2x la a doua-2 x +6x-6=-5
4x la a doua + 7x-5=-5
4x la a doua + 7x=-5+5
4x la a doua + 7x =0
Alte întrebări interesante
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă